2011
DOI: 10.1007/s12672-011-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

Role for MicroRNAs in Regulating Glucocorticoid Response and Resistance in Multiple Myeloma

Abstract: Glucocorticoids (GCs) are widely used in the treatment of hematological malignancies such as multiple myeloma. However, the development of resistance to GCs limits their clinical utility. Response to GCs is dependent on an active glucocorticoid receptor, GR-α, expressed at wild-type levels in the GC-sensitive cell line (MM.1S). GC-resistant derivative cell lines MM.1Re and MM.1RL display significant downregulation of GR-α transcripts. In this study, we report that a luciferase reporter containing the 3′-UTR of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 34 publications
(32 reference statements)
2
51
0
Order By: Relevance
“…Previously, it has been shown that miR-130b regulates the glucocorticoid receptor on protein level in multiple myeloma (Tessel et al, 2011). Furthermore, the glucocorticoid receptor has been shown to regulate the transcription of CAR (Pascussi et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been shown that miR-130b regulates the glucocorticoid receptor on protein level in multiple myeloma (Tessel et al, 2011). Furthermore, the glucocorticoid receptor has been shown to regulate the transcription of CAR (Pascussi et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Levels of GR may also be influenced by miRNA. In multiple myeloma cells, miR-130b inhibits GR and protein expression (29). Hydrocortisone-induction of miR-124 expression in lymphocytes is associated with the downregulation of the GR alpha (30).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that miR-124 specifi cally downregulated GR-α, and a slight increase of miR-124 and a reduction of GR-α were observed in patient T cells compared with healthy controls [ 108 ]. In addition, Tessel and colleagues [ 109 ] identifi ed and characterized miR-130b as an important downregulator of GR in a GC-resistant multiple myeloma cell line: The overexpression of this miRNA was also associated with a decreased regulation of GILZ , a downstream GC-controlled gene (Table 2 ).…”
Section: Mirnas Involved In Gr Regulation and Their Potential Rolementioning
confidence: 97%